Chains - Anderson, Laurie Halse (New York : Scholastic Inc., 2009)
After being sold to a cruel couple in New York City, a slave named Isabel spies for the rebels during the Revolutionary War.
Reprint: Originally published: New York : Simon & Schuster Books for Young Readers, 2008.
"First Scholastic printing, September 2009"--Title page verso.
"This edition is available for distribution only through the school market."--Page 4 of cover.
Ages 10 up.
National Book Award Finalist, Young People's Literature, 2008
Scott O'Dell Award for Historical Fiction, 2009
Keywords: New York (N.Y.) -- History -- Revolution, 1775-1783 -- Juvenile fiction; New York (N.Y.) -- History -- Revolution, 1775-1783 -- Fiction; United States -- History -- Revolution, 1775-1783 -- Fiction; Slavery -- Fiction; African Americans -- Fiction; Spies -- Fiction